The Consequences of Petrophysical Effects on Reservoir Properties of Hartha Formation at Balad Oil Field, Central Iraq - Albarzanji, Pishwar Kh.; Alhamdani, Saad A. (Journal of Petroleum Research and Studies, 2024)
Hartha Formation (Upper Companian-Mastrechtian Sequence) consists mainly of detrital organic limestone and dolomitic limestone and may contains streaks of marl and through the petrographic study of the rocks of the formation, it was found that it consists of skeletal granules consisting of benthic foraminifera represented by fossils (orbitoid, rotalide and miliolide) and a few planktonic foraminifera belonging to the family of Globigerinacea and red, green algae, echinoderms, mollusks and the Formation also contained a few Calcispheres and these granules appeared affected by several modifying processes, the most important of which are Dolomitization, recrystallization, dissolution, Micritization and chemical compression and it was found through the analysis of the Microfacie that the Formation consists of four main, microfascies the upper limit of the Formation is conformable with the Formation of the Shiranish, while the lower limit represents unconformable with the Formation of Mashura. The present study focused on the effect of Diagenesis processes on the Hartha Formation in four subsurface sections within the Balad field in Salah al-Din Governorate in central Iraq, representing the first section (Ba-1) with a thickness of (443) m, the second section (Ba-5) with a thickness of (306) m, the third section (Ba-7) with a thickness of (306) m. (Ba-9) and thickness (307) m. Where (355) slides consisting of rock cutting and cores were studied, (144) slides for the well (Ba-1), (58) slides for the well (Ba-5), (54) slides for the well (Ba-7) and in the well (Ba-9). It was by (99) slides, as well as the logs of the above wells, through which the Formation was divided into three porous units.